Use of the Rorschach test in the works of A.R. Luria - E.Y. Nikonova; G.E. Rupchev; T.V. Akhutina (Культурно-историческая психология)
The article is devoted to the analysis of the only surviving protocol of the Rorschach test, which was conducted by A.R. Luria as part of aphasia research. The study, performed in 1933, was aimed at investigating the role of speech in behavior in patients with organic brain lesions. Patient Avt. suffered from amnestic aphasia, unilateral hemianopsia, and disorders of the cognitive and emotional spheres associated with the late stage of neurosyphilis. A.R. Luria made a detailed individual plan of examination of Avt. and used the Rorschach test cards to reveal the patient's ability for voluntary speech and analysis of visual images. The article presents a transcription and modern interpretation of Auth's protocol, which demonstrates the peculiarities of the patient's perception and thinking: fragmentary images, difficulties in integrating visual stimuli, internal speech disorders, as well as reliance on autobiographical memories and a tendency to “self-recognition”. Hemianopsia hampered the perception of symmetrical Rorschach patches, and cognitive impairment limited the ability to think coherently and form coherent images. Nevertheless, individual patient responses indicated that basic perception was preserved, which was analyzed in detail. The analysis revealed increased anxiety, dysphoria, and hypochondria in Auth's responses. The final part of the article discusses subsequent references to the Rorschach test in A.R. Luria's works and his negative attitude toward using this technique in neuropsychology, given its greater suitability for analyzing the emotional and personal sphere.